Manejo y disposición de (RCD), su incidencia en el medio ambiente, una revisión bibliográfica (2023)
The global generation of construction and demolition Waste (CDW) is constantly increasing, driven by continuous urban development. In this context, it is imperative to implement adequate management of this waste to mitigate its environmental impact. The improper disposal of Construction and Demolition Waste (RCD) can lead to profound consequences for the environment, affecting soil, water bodies, air, and natural resources. This project focuses on examining the current situation of CDW, addressing existing regulations, and considering the material's value chain. The importance of selective classification of these wastes is emphasized, and the main impacts resulting from a lack of timely management and disposal are analyzed. The adverse consequences that may arise when these wastes interact with various environmental modifying substances are explored in detail. The goal of this monograph is the creation of an informative article and a pamphlet. These materials aim to provide readers with a comprehensive understanding of the environmental implications associated with CDW, while also presenting feasible alternatives for their utilization.